2008
DOI: 10.1002/sia.2724
|View full text |Cite
|
Sign up to set email alerts
|

Determination of wettability of surface‐modified hot‐embossed polycarbonate wafers used in microfluidic device fabrication via XPS and ToF‐SIMS

Abstract: The wettability of the surfaces inside the microchannels of a microfluidic device is an important property considering a liquid flows through them. Contact angle measurements usually applied to test the wettability of surfaces cannot be used for an analysis of microchannel walls within microfluidic devices. A workaround is the use of surface analytical methods, which are able to reach points of interest in microchannels and may provide information on the surface chemistry established there. In calibrating thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…Thus an indirect approach for predicting contact angle is of direct benefit to industries where wettability is crucial but contact angle measurements cannot be directly acquired. To overcome this limitation, Baytekin et al [2] have demonstrated the use of surface analytical methods such as time-of-flight secondary ion mass spectrometry (ToF-SIMS) and X-ray photoelectron spectroscopy to study points of interest in microfluidic devices and provide information on the surface chemistry established there. By using flat reference polymer wafers made from the same material, where the contact angle can be measured as usual, appropriate calibration curves can be established.…”
Section: Introductionmentioning
confidence: 99%
“…Thus an indirect approach for predicting contact angle is of direct benefit to industries where wettability is crucial but contact angle measurements cannot be directly acquired. To overcome this limitation, Baytekin et al [2] have demonstrated the use of surface analytical methods such as time-of-flight secondary ion mass spectrometry (ToF-SIMS) and X-ray photoelectron spectroscopy to study points of interest in microfluidic devices and provide information on the surface chemistry established there. By using flat reference polymer wafers made from the same material, where the contact angle can be measured as usual, appropriate calibration curves can be established.…”
Section: Introductionmentioning
confidence: 99%
“…X-ray Photoelectron Spectroscopy (XPS) measurements reveal that oxygen content on the surface is increased, carbon content is depleted while oxygen functional groups are formed such as carbonyl (-C=O), carboxyl (-COOH) and carbonate (CO 3 ) [21,[26][27][28]. The appearance of functional groups increases the surface free energy of the material.…”
Section: Resultsmentioning
confidence: 99%
“…In general, these polymers are hydrophobic in nature and the control of the wettability requires additional surface treatments. The surface modification techniques employed up to now in hot-embossed polymers typically resort either to plasma treatments [41,42] or to the formation of self-assembled monolayers (SAMs) [43]. However, such treatments have been demonstrated to have a limited lifetime.…”
Section: Introductionmentioning
confidence: 99%